Burnout, Loyalitas, Dan Kesejahteraan Guru: Analisis Isu Kontemporer Manajemen Sumber Daya Manusia Di Madrasah Aliyah Barokatul Qodiri Banyuasin - Else Meina; Siti Sumartini; Baktina Damayanti; Kasinyo Harto; Febriyanti Febriyanti (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the phenomena of burnout, loyalty, and teacher well-being in the context of human resource management at Madrasah Aliyah Barokatul Qodiri Banyuasin. This study uses a qualitative approach with a case study research type. Interviews were conducted with the madrasah principal, curriculum deputy, senior teachers, middle teachers, new teachers, and administrative staff. The results show that burnout is triggered by high administrative burdens, excessive teaching hours, accreditation demands, and psychological stress. Teacher loyalty is influenced by financial and non-financial well-being, performance-based rewards, professional development opportunities, managerial support, a religious and familial work culture. Effective human resource management strategies, including workload redistribution, mentoring, training programs, counseling, and spiritual guidance, have been shown to increase loyalty, reduce the risk of burnout, and support the quality of continuous learning.